EVALUATING AND RATING THE PERFORMANCE OF DSWIM USING ANSYS MAXWELL (International Journal of Food and Nutritional Sciences, 2021)
Induction motors are popular in the industrial and agricultural sectors due to their durable design, low cost of ownership, efficient operation, low maintenance requirements, and consistent performance under a variety of loading conditions. As a result, the researcher has a strong desire to improve performance to a higher extent. This idea suggests the use of two separate stator windings, each with a different number of poles, on a standard induction motor's shared cage rotor. The Finite Element Method (FEM) is used in this study to provide a thorough assessment of the Dual Stator Winding Induction Machine (DSWIM). ANSYS Maxwell and RMxprt are the software packages used for the design and analysis of DSWIM (Direct-Driven Synchronous Windings Induction Machine).The output of RMxprt is a complete design sheet that includes the machine's important parameters and performance indicators. The ANSYS Maxwell program can be used to evaluate electromagnetic properties such as flux charts and to generate three-dimensional and two-dimensional models. This design and simulation aid in correcting any inadequacies in the building or operation of the equipment prior to the probable occurrence of any negative impacts.